Classification and Volume Coordination Tasks of Organization Activity and Behavior - V. M. Merkulov (Управленческое консультирование, 2021)
Based on the process approach, the article classifes the types of coordination tasks of different complexity and forms. Factors of inﬂuence on labor intensity of coordination tasks of activities and behavior are identifed. It is proposed to group factors of inﬂuence on the standard of manageability in connection with the solution of coordination tasks. The need and composition of the tasks of using informal relations and structure in coordination are justifed.